Point of no return for improvement of cartilage quality indicated by dGEMRIC before and after weight loss in patients with knee osteoarthritis: a cohort study. (March 2018) - Hangaard, Stine; Gudbergsen, Henrik; Skougaard, Marie; Bliddal, Henning; Nybing, Janus D; Tiderius, Carl Johan; Boesen, Mikael
Background: It has been demonstrated that weight loss improves symptoms in obese subjects with knee osteoarthritis (KOA). A parallel change in cartilage morphology remains to be demonstrated. Purpose: To demonstrate a parallel change in cartilage morphology. Material and Methods: Obese patients with KOA were examined before and after weight loss over 16 weeks. Target knee joints were radiographically assessed by the Kellgren/Lawrence grading (KLG) system. Patients with KLG-1 and 2 changes in the lateral compartment were included. Delayed gadolinium-enhanced MRI of cartilage (dGEMRIC) was performed using intra-articular contrast. Results: Nine patients with lateral KLG-1 and ten patients with lateral KLG-2 were studied. There were no group differences regarding the lateral compartment baseline dGEMRIC T1 values: median = 497 ms (KLG-1) and 533 ms (KLG-2) ( P  = 0.12), or regarding reduction in body mass index (BMI) after 16 weeks: 12.8% versus 11.4% ( P  = 0.74). In the KLG-1 group, several cases of increased dGEMRIC T1 values were seen and median value decreased significantly less than in KLG-2 group (15 ms versus 41 ms, P  = 0.03) after weight loss. Conclusion: Improvement of cartilage quality, assessed with dGEMRIC, after weight loss might be possible in early stage KOA (KLG-1), but not in later stage KOA (KLG-2). The results may suggest a point of no return for improvement of cartilage quality that should be tested in larger trials.